Growth, yield and quality response of Eggplant (Solanum melongena L.) to blended NPSB fertilizer rates and intra-row spacing in Boloso Bombe district, Wolaita zone, South Ethiopia - Yitbarek Abrham; Abrham Shumbulo (Heliyon, 2024)
Eggplant is the most important fruit vegetable crop in many countries, including Ethiopia. In spite of this, its production is hindered by low nutrient availability in soil and suboptimal intra-row spacing. In order to address these issues, a field investigation took place in the Wolaita zone during 2022/23 growing season to evaluate the effects of various concentrations of blended NPSB fertilizer and intra-row spacing on the growth, yield, and quality of eggplants. Five various blended NPSB fertilizer rates (0, 50, 100, 150, and 200 kg ha−1) and three intra-row spacing distances (30, 40, and 50 cm) were used in the investigation, which was designed as a randomized complete block with three replicates. Based on an analysis of variance, it was discovered that the main effects of NPSB fertilizer rates and intra-row spacing significantly (p < 0.01) affected many of parameters, including dry matter content, total soluble solids, fruit number, fruit length, and days to 50 % flowering. Additionally, the interaction effect between NPSB fertilizer and intra-row spacing significantly (p < 0.05) impacted the number of days to first fruit harvest, plant height, leaf area, branch number, leaf number, fruit diameter, fresh fruit yield, marketable fresh fruit yield, unmarketable fresh fruit yield, and total fresh fruit yield. According to the current investigation, the highest marketable fresh fruit yield (121.04 t ha−1) was obtained by 150 kg ha−1 NPSB with 40 cm intra-row spacing. These findings suggest that 150 kg ha−1 of blended NPSB fertilizer with 40 cm distance between plant spacing is optimal for eggplant cultivation in the study area and analogous agro-ecological settings. This optimized approach can effectively support eggplant growers in maximizing both yield and quality outcomes.